Concentrations of Co-Administered Meropenem and Vancomycin in Spinal Tissues Relevant for the Treatment of Pyogenic Spondylodiscitis-An Experimental Microdialysis Study - Josefine Slater; Maiken Stilling; Pelle Hanberg; Sofus Vittrup; Martin Bruun Knudsen; Sara Kousgaard Tøstesen; Josephine Olsen Kipp; Mats Bue (MDPI AG, 2023)
Co-administration of meropenem and vancomycin has been suggested as a systemic empirical antibiotic treatment of pyogenic spondylodiscitis. The aim of this study was, in an experimental porcine model, to evaluate the percentage of an 8-h dosing interval of co-administered meropenem and vancomycin concentrations above the relevant minimal inhibitory concentrations (MICs) (%T>MIC) in spinal tissues using microdialysis. Eight female pigs (Danish Landrace breed, weight 78-82 kg) received a single-dose bolus infusion of 1000 mg of meropenem and 1000 mg vancomycin simultaneously before microdialysis sampling. Microdialysis catheters were applied in the third cervical (C3) vertebral cancellous bone, the C3-C4 intervertebral disc, paravertebral muscle, and adjacent subcutaneous tissue. Plasma samples were obtained for reference. The main finding was that for both drugs, the %T>MICs were highly reliant on the applied MIC target, but were heterogeneous across all targeted tissues, ranging from 25-90% for meropenem, and 10-100% for vancomycin. For both MIC targets, the highest %T>MIC was demonstrated in plasma, and the lowest %T>MIC was demonstrated in the vertebral cancellous bone for meropenem, and in the intervertebral disc for vancomycin. When indicated, our findings may suggest a more aggressive dosing approach of both meropenem and vancomycin to increase the spinal tissue concentrations to treat the full spectrum of potentially encountered bacteria in a spondylodiscitis treatment setting.